2000
DOI: 10.1002/1529-0131(200007)43:7<1647::aid-anr31>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of muscarinic receptor autoantibodies on parasympathetic neurotransmission in Sjögren's syndrome

Abstract: Objective. Sjögren's syndrome (SS) is an auto-immune disorder characterized by dry eyes and mouth (sicca syndrome) and lymphocytic infiltration of the lacrimal and salivary glands. Abnormalities of para-sympathetic neurotransmission may contribute to the glandular dysfunction. In this study, we used a functional assay to investigate autoantibody-mediated effects on parasympathetic neurotransmission and smooth muscle contraction. Methods. Serum and purified IgG were obtained from patients with primary and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 20 publications
8
79
0
2
Order By: Relevance
“…Recent studies suggest that autoantibody to M3R may cause secretory dysfunction that leads to dry mouth in patients with Sjögren's syndrome. 10,25,26 Studies have also shown that sera from patients with Sjögren's syndrome inhibit smooth muscle contraction of isolated bladder strips in response to stimulation of M3R by a muscarinic receptor agonist. Autoantibody to M3R may explain manifestations of autonomic dysfunction, such as interstitial cystitis, in some patients with Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that autoantibody to M3R may cause secretory dysfunction that leads to dry mouth in patients with Sjögren's syndrome. 10,25,26 Studies have also shown that sera from patients with Sjögren's syndrome inhibit smooth muscle contraction of isolated bladder strips in response to stimulation of M3R by a muscarinic receptor agonist. Autoantibody to M3R may explain manifestations of autonomic dysfunction, such as interstitial cystitis, in some patients with Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that autoantibody to type 3 muscarinic acetylcholine receptor (M3R) may contribute to sicca symptoms and may explain associated features of autonomic dysfunction in some patients. 10 Interstitial cystitis accompanying Sjögren's syndrome was first reported by Van De Merwe and colleagues in 1993. 7 To the best of our knowledge, only three reports on interstitial cystitis accompanying Sjögren's syndrome have been published in Japan over the last 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to functionally analyze anti-M3R antibodies. For example, assays of smooth muscle showed that IgG fractions from patients with SS (SS-IgG) inhibited carbachol-evoked or nerveevoked bladder or colon contractions, respectively [5,6]. In salivary gland cells, SS-IgG inhibited both the rise in [Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…Die Autoantikörper können für den Verlust der sekretorischen Funktion der Drüsen z. T. verantwortlich sein. Die Prä-valenz der Autoantikörper beim primären Sjögren-Syndrom beträgt etwa 60%, die Spezifität ist bei einer Prävalenz von 12% bei Blutspendern aber gering [25]. Der Marker wird momentan nur aus Forschungsindikation bestimmt.…”
Section: Antikörper Gegen M 3 -Muskarinische Acetylcholinrezeptorenunclassified